2006
DOI: 10.1088/0026-1394/43/1a/08010
|View full text |Cite
|
Sign up to set email alerts
|

International Comparison CCQM-P28: Ozone at ambient level

Abstract: We report a pilot study organized within the Consultative Committee for Amount of Substance (CCQM), in which the ozone reference standards of 23 institutes have been compared to one common reference, the BIPM ozone reference standard, in a series of bilateral comparisons carried out between July 2003 and February 2005. The BIPM, which maintains as its reference standard a standard reference photometer (SRP) developed by the National Institute of Standards and Technology (NIST, United States), served as pilot l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…A second ozone standard is gas phase titration of ozone against nitric oxide gas standards. Differences between GPT and standard UV photometry have been investigated by Tanimoto et al (2006) and Viallon et al (2006bViallon et al ( , 2016 and found to be very small (~0.3%) when the newer values of the ozone absorption cross-sections (see Section 2.2.1) are used . Thus GPT supports the proposed decrease in the ozone absorption cross-section at 253.65 nm.…”
Section: Standards For the Measurement Of Ozone In The Atmospherementioning
confidence: 99%
“…A second ozone standard is gas phase titration of ozone against nitric oxide gas standards. Differences between GPT and standard UV photometry have been investigated by Tanimoto et al (2006) and Viallon et al (2006bViallon et al ( , 2016 and found to be very small (~0.3%) when the newer values of the ozone absorption cross-sections (see Section 2.2.1) are used . Thus GPT supports the proposed decrease in the ozone absorption cross-section at 253.65 nm.…”
Section: Standards For the Measurement Of Ozone In The Atmospherementioning
confidence: 99%
“…In addition, by limiting measurements to the strongest absorbing region of the spectrum, close to 255 nm, all measurements can be performed with a single absorption cell, over a limited ozone pressure range and in a limited time to avoid ozone decay due to dissociation, as reported by Mauersberger et al (1985Mauersberger et al ( , 1986Mauersberger et al ( , 1987. This group reported two values of the cross-section having a small relative standard uncertainty (0.5 and 0.7 %), and with values smaller by 0.8 and 1.4 % compared to the 1961 value reported by Hearn. During the first international comparison of ozone standards for ground-level ozone conducted by the BIPM, 23 laboratories reported results based on UV absorption compared to two laboratories reporting ozone concentration measurements based on gas phase titration systems: the National Institute for Environmental Studies of Japan as described by Tanimoto et al (2006) and the BIPM (Viallon et al, 2006a). Gas phase titration involves reacting ozone in air with nitrogen monoxide, and measuring either the loss of nitrogen monoxide or the gain of the reaction product, nitrogen dioxide, to deduce the ozone concentration in the sample.…”
Section: Introduction and Aimsmentioning
confidence: 99%
“…During the first international comparison conducted by the BIPM [ Viallon et al , 2006a], 23 instrument standards based on UV absorption (same measurement principle as that of the SRP) were compared together with two systems based on gas‐phase titration, an independent method for ozone concentration measurements, maintained by the BIPM and by the National Institute for Environmental Studies of Japan [ Tanimoto et al , 2006]. Gas‐phase titration consists of mixing the ozone in air sample with nitrogen monoxide and measuring either the loss of nitrogen monoxide or the gain of the reaction product, nitrogen dioxide, to deduce the ozone concentration in the sample.…”
Section: Introduction and Aimsmentioning
confidence: 99%